Analysis of Strategic Risk Management of National Board of Zakat (BAZNAS) in Sukabumi - Hartomi Maulana Maulana; Soritua Ahmad Ramdani Harahap Harahap; Mentari Fazrinnia Fazrinnia (Faculty of Economics and Management, 2022)
Zakat is one of the five basic pillars of Islam. The main function of zakat is to help the economy of the mustahik and become a counterweight in the national economic sector. Government Regulation of the Republic of Indonesia explained that the management of zakat is regulated by a non-structural government agency, namely, the National Board of Zakat (BAZNAS) which is responsible to the President through the Minister. The inaugural meeting of the International Working Group on Zakat Core Principles, which resulted in an agreement that the identification of risks in zakat management is very important because it will affect the quality of zakat management in the future. The purpose of this study was to analyze the implementation and mitigation of strategic risk management in the BAZNAS in Sukabumi. This study employs quantitative approach as research method. Interview and documentation are used as data collection techniques. The results of this study found that implementation of strategic risk management and the mitigation of strategic risk of BAZNAS in Sukabumi is well implemented. The vision and mission risk is the biggest strategic risk that is likely to occur, while the strategic risk that has the greatest impact is the objective risk. The BAZNAS in Sukabumi has good risk mitigation based on the scale of risk vulnerability.